Combining rTMS With Intensive Language-Action Therapy in Chronic Aphasia: A Randomized Controlled Trial - Heikkinen, Paula H.; Pulvermüller, Friedemann; Mäkelä, Jyrki P.; Ilmoniemi, Risto J.; Lioumis, Pantelis; Kujala, Teija; Manninen, Riitta-Leena; Ahvenainen, Antti; Klippi, Anu (Frontiers in Neuroscience, 2019)
New neuromodulation technologies, such as transcranial magnetic stimulation (TMS), are promising tools for neurorehabilitation, aphasia therapy included. Combined with behavioral techniques, in particular treatment-efficient Intensive Language-Action Therapy (ILAT, previously CIAT or CILT), TMS could substantially amplify the beneficial effect of such behavioral therapy alone (Thiel et al., 2013; Martin et al., 2014; Mendoza et al., 2016; Kapoor, 2017). In this randomized study of 17 subjects with post-stroke aphasia in the chronic stage, we studied the combined effect of ILAT and 1-Hz placebo-controlled navigated repetitive TMS (rTMS) to the right-hemispheric inferior frontal cortex – that is, to the anterior part of the non-dominant hemisphere’s homologue Broca’s area (pars triangularis). Patients were randomized to groups A and B. Patients in group A received a 2-week period of rTMS during naming training where they named pictures every ten second displayed on the screen, followed by 2-weeks of rTMS and naming combined with ILAT. Those in group B received the same behavioral therapy but TMS was replaced by sham stimulation. The primary outcome measures for changes in language performance were the Western Aphasia Battery’s aphasia quotient AQ; the secondary outcome measures were the Boston naming test (BNT) and the Action naming test (Action BNT, ANT). All subjects completed the study. At baseline, no statistically significant group differences were discovered for age, post-stroke time or diagnosis. ILAT was associated with significant improvement across groups, as documented by both primary (F(1,15)=23.969, p=0.001, η2=0.641) and secondary outcome measures. No significant effect of rTMS could be documented. A ceiling effect for magnetic stimulation was ruled out by numerically lower performance in the TMS group compared with that receiving sham stimulation. Our results agree with previous results proving ILAT’s ability to improve language in patients with chronic aphasia. However, in contrast with earlier claims, a beneficial effect of rTMS in chronic post-stroke aphasia rehabilitation was not detected in this study.